Gambaran Efektivitas Kepemimpinan Bina Nusantara Computer Club Kepengurusan ke-22 Berdasarkan Fiedler’s Contingency Model - Eleonora Francisca Maria Sumual; Juliana Lee (Bina Nusantara University, 2011)
Fiedler has theory which is called “contingency model”. According to him, if an organization attempts to achieve group effectiveness through leadership, then there is a need to assess the leader according to an underlying trait, assess the situation faced by the leader, and construct a proper match between the two. With Fiedler model, researchers were doing assessment to one of the student organization in Bina Nusantara University, which is BNCC 22nd student committee. The result of the research is that student organization in this case two committees from BNCC show two different results. The first one does not fit with Fiedler model, which is the “people oriented” leader can make an effective leadership, and the second one with “people oriented” leader seems not effective to lead the committee with more old member of the organization.